THE ESTIMATION OF WEATHER-CLIMATIC FACTORS’ EFFECT ON THE LEVEL OF YIELD OF BUCKWHEAT CERTIFIED SEEDS - Tryhub, O. V.; Kutsenko, O. M.; Marenych, M. M.; Liashenko, V. V. (Scientific Progress & Innovations, 2020)
At present, buckwheat belongs to niche crops because of its dependence on the environmental weatherclimatic conditions, which negatively affect its highly productive potential (yield and produce quality). At the same time, the level of buckwheat consumption in Ukraine exceeds the volumes of its cultivation, which stipulates the import of doubtful quality buckwheat. That is why the necessity arises as to increasing the government support of the national producers of goods, creating and introducing in the production of cultivars having high yield potential under changes of natural-climatic factors. The article presents the results of studying the material of 257 varieties and forms of common buckwheat of different ecological and geographical origin from the National Collection of Ukraine on the basis of the Ustymivska Experimental Station of Plant Growing for the period of 2014–2018. The field experiments were conducted in selection-seed crop rotation, winter grain crops of the previous year were the proceeding crops, and generally accepted technology of buckwheat cultivation was used. The statistical data processing and correlation, variance analyses were conducted by the methods of B. A. Dospekhov. The studied material was divided into two groups according to ripeness parameters: early ripening and mid-ripening, with further analysis of each of them. For the study and analysis, the parameters of the duration of the entire growing season and the period “flowering – the beginning of ripening”, as the most critical parameter for the harvest, according to preliminary studies, were taken. Different levels and various tendencies were revealed as to weather-climatic conditions’ influence on the crop yield level depending on ripeness level of the collection material, which can be a significant factor in the study of buckwheat initial material for different zones and directions of using. The possibility of using hydro-thermal coefficient as an integral indicator in determining the total effect of climatic factors on yield characteristics of buckwheat was proven, the description of their biological and morphological peculiarities was given.